2011
DOI: 10.1002/jsfa.4337
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of glucose uptake byMusasp. (cv. elakki bale) flower and pseudostem extracts in Ehrlich ascites tumor cells

Abstract: Banana flower and pseudostem extracts are able to promote glucose uptake into the cells, presumably through glucose transporters 1 and 3, which could be beneficial in diabetes. Glucose uptake is likely promoted by phenolic acids besides other bioactives. It can be hypothesized that consumption of nutraceutical-rich extract of banana flower and pseudostem could replace some amount of insulin being taken for diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…cv. Elakki bale and M. paradisiaca flowers on the improvement in glucose uptake . Both evaluated the uptake of glucose using its fluorescent analogue 2‐[N‐(7‐nitrobenz‐2‐oxa‐1,3‐diazol‐4‐yl)amino]‐2‐deoxy‐D‐glucose (2‐NBDG).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…cv. Elakki bale and M. paradisiaca flowers on the improvement in glucose uptake . Both evaluated the uptake of glucose using its fluorescent analogue 2‐[N‐(7‐nitrobenz‐2‐oxa‐1,3‐diazol‐4‐yl)amino]‐2‐deoxy‐D‐glucose (2‐NBDG).…”
Section: Resultsmentioning
confidence: 99%
“…Ehrlich ascites tumour (EAT) cells were chosen as a cellular model by Bhaskar and colleagues . This model was also utilized in other studies of glucose transport .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The extract has anti-oxidant property that prevents free radicals and control cell and tissue damage. Bhaskar et al, (2011) reported that glucose uptake in Ehrlich ascites tumor cells was stimulated by banana (Musa sp.) flower and pseudostem extracts.…”
Section: Introductionmentioning
confidence: 99%